Chaos at the Lazy Bones Bookshop - Duncan, Emmeline (Kensington Publishing Corp., 2024)
"Bailey Briggs adores her year-round Halloween-themed town of Elyan Hollow, Oregon, but when she takes over her grandfather's beloved bookshop, Lazy Bones Books, she accidentally discovers the town's secret dark side... Normally, spooky season is Bailey Briggs' favorite time of year, and her Halloween-themed small town's time to shine. But between managing Lazy Bones Books, working on her graphic novel-in-progress, and running the Spooky Season Literary Festival, Bailey hardly has a moment to enjoy Elyan Hollow's spot-on seasonal vibes. Not to mention, at every turn she seems to be tripping over the contentious crew of Gone Ghouls, a ghost-hunting reality TV show currently filming around town. Bailey tries to stay focused on the Lit Festival, which is supposed to kick off Elyan Hollow's annual Halloween Fair; instead, this year's festival begins with a murder... It's bad enough Bailey discovered the victim, but now, as a lead suspect with some (admittedly) damning evidence pointing her way, she's got to clear her name! With the help of her librarian friend, Colby, and Jack Skeleton, her world-class bookshop dog (and the absolute bestest boy ever), Bailey sets out to solve a murder... As her investigation weaves through family secrets, professional rivalries, and town feuds, the list of suspects is growing fast... and unfortunately, so is the list of victims. If Bailey doesn't find the killer soon, Elyan Hollow's haunted reputation will get a little too real..." -- Back cover.